BARRON'S : ESSENTIAL WORDS FOR THE IELTS - Lougheed, Lin , 1946- (Barron's Educational Series, Inc., 2017)
Reviews all question types covered by the International English Language Testing System, offers four practice tests, and includes audio portions of the test on CDs.